An ecosystem approach to malaria control in an urban setting - Gabriel Carrasquilla (Cadernos de Saúde Pública, 2001)
We conducted a research project aimed at strengthening local government and the community for a sustainable malaria control strategy. The project began with a baseline diagnosis of malaria prevalence, a KAP survey, entomology, and health services delivery, after which an epidemiological study was performed to identify risk factors associated with malaria, thereafter used to plan intervention measures. A program evaluation was conducted five years later. By using an ecosystem approach to reanalyze data, this paper discusses how malaria arises from a complex interaction of cultural, economic, ecological, social, and individual factors. Intervention measures require an intersectorial and transdisciplinary approach that does not exist at the moment. Health sector leadership is limited, and there is no true community participation. Implications for research, including the use of qualitative and quantitative methods, study design, and complexity of data analysis are discussed. Finally, implications for malaria control are discussed, stressing the differences between the ecosystem and integrated disease control approaches.